Perbandingan CPOT dan Comfort Scale sebagai Instrumen Nyeri Pasien yang Terpasang Ventilator di ICU RSUP Dr. Soeradji Tirtonegoro Klaten - Kurnia Devi Saraswati; Rosa Delima Ekwantini; Sari Candra Dewi (Caring : Jurnal Keperawatan, 2020)
Background: Ventilator is arespiratory aids was used for respiratory failure patient. Critical condition of patients with ventilators will have caused physical, psychosocial and spiritual problems. A ventilator tube in the throat caused patient could not speak, pain and discomfort. Assessment of pain in critical patients with ventilator is very necessary because of the inability the patient for verifying. The Critical-Care Pain Observation Tool (CPOT) and Comfort Scale are pain assessment instruments for adult patients. Purpose: This study aims to determinated comparation validity and reliability of Critical-Care Pain Observation Tool (CPOT) and Comfort Scale as pain instrument in patient installed ventilator at the ICU RSUP Dr.Soeradji Tirtonegoro Klaten Method: This research was used a cross sectional design. Sampling was used consecutive sampling technique. Respondents were assessed two times before and after suction using the CPOT and Comfort Scale instruments. The samples of this research are 30 respondents. This research was conducted in February-March 2020. The data has been analyzed using Receiver Operating Curve (ROC) and Kappa Cohen. Study Result: The result of the CPOT instrumen had a kappa value of 1, sensitivity of 100%, specificity of 73,08% with AUC area of 0,875. While the Comfort Scale instrumen had a kappa value of 1, a sensitivity of 54,55%, specificity of 100% with AUC area of 0,830.